Aetxara’u e a memória da pele ou “que faço com minha cara de índia”? : o encontro com a auto-história teoria. - Silva, Janaína (2023)
The present interdisciplinary paper, which aims to narrate a path of resumption of indigenous ancestry, identity and spirituality (Potiguara 2004), in the structures of the production of academic knowledge - a path that is understood here as life-thought-theory. We will look at the concept of autohistoria-teoría, developed by Gloria Anzaldúa in her works; The text constitutes a dialogue with the writer, poet and indigenous activist Eliane Potiguara (Potiguara 2018), who narrates the story lived by the women in her family throughout the Brazilian colonization process, starting from her journey of resumption, whose process involves understanding herself, added the investigation of the process of forced migrations in the territories of their ancestors and the political articulation configured from the resumption; reflections on decolonizing methodologies that affirm indigenous authorship in academic research spaces . The crossroads of these three references is added to the gathering of material and immaterial traces of memory such as family objects, reports of indigenous and black women, their ancestry and spirituality practiced in their relationship with the land and with food and herbs, brought, within the scope of this research, as elements or devices of memory. As critical fabulation is a resource to face epistemicides, ethnocides, erasures and twists of history, present in this struggle between worlds and words. Like the struggle between worlds, of the nepantla condition (Anzaldúa 2005), writing as an enunciative possibility in the field of anticolonial imagination, in a transit between social and identity borders, between languages and in a continuous process of updating and reinscribing the autobiographical narrative as an affirmation of reality about our existences and ancestors.